Avaliação dos efeitos do estresse pré-natal sobre parâmetros comportamentais e pulmonares em camundongos - Vargas, Mauro Henrique Moraes (2013)
Introduction : The prenatal period is critical for the development and maturation of several organ systems essential. Objective : To evaluate the effects of prenatal stress on behavioral responses, as well as possible structural changes and standard cell lung in an experimental model with Balb/c. Materials and Methods : We used female Balb/c primiparous. After identification of pregnancy, the animals were divided into 3 groups: CTLE (control), PNS 1 (stress every other day from the 8th day of pregnancy) and PNS 2 (stress from day 15 of pregnancy until birth). The prenatal stress was accomplished through containment. The animals were weighed at birth, weaning and day 10 (day 21). As adults, we analyzed the behavior of fear/anxiety through field tests (AC) and elevated plus maze (EPM) was performed and bronchoalveolar lavage (BAL) and lung histopathology. Results : No differences were found in relation to animal weight among the three groups. Behavioral analysis of the males in the test AC and EPM, showed no significant difference between groups PNS 1 and PNS 2 relative to CTLE. In the analysis of the test AC, females PNS 1 group showed a decrease in the total distance covered (P <0.001) increased time on the periphery (p <0.001) and decreased time the center (p <0.001) compared to the group CTLE. The test EPM in females was not significantly different among the three groups. The analysis of the cellular profile in BAL and lung histology, there were no differences between groups. Conclusion : The prenatal stress induces changes in the behavior of fear/anxiety only in Balb/c mice and the stress model from the eighth day of pregnancy, suggesting that the effects of the programming are possible in this model. On the other hand, prenatal stress caused no alterations in basal lung.